Effect of 12-Week Progressive Resistance Training on Balance, Fatigue and Disability in Women with MS - Asghar Tofighi; Yaghob Saki; Keyvan (Majalah-i ̒ilmī pizishkī-i jundī/shapūr, 2013)
Background and Objective: Multiple Sclerosis (MS) is a demyelinating disease of the central nervous system (CNS) which leads to myelin distraction and disfunction in nerve conduction. The purpose of this study was to evaluate the effect of 12-week progressive resistance training on balance, disability and fatigue in women with MS. Subjects and Methods: Based on a quasi experimental method, 24 women with MS (30.5 ± 5.9 years old, 68± 11 kg, height 160± 7.6 cm) with 1 to 4 Expanded Disability Status Scale (EDSS) degree participated and randomly divided into two control and experimental groups. Experimental group carried out a 12-week resistance exercise program for 45 to 60 min 3 times/week. Control group did not participate in any routine exercise regimen. Berg Balance Scale test (BBS) was used to assessment of balance. In addition, fatigue severity scale (FFS) and EDSS questioners were used to evaluate fatigue and disability respectively. Data were analyzed by Multiple Analyses Of Variance (MANOVA) method with SPSS software at P<0.05.Results: A significant difference in average scores of balance and fatigue between control and experimental groups (P<0.05), However, no significant difference was found in average scores of EDSS (P>0.05).Conclusion: 12-week resistance training increases balance and decreases fatigue in MS patient; however, has no positive effect on disability.